A CLINICAL EFFECT OF TRIVRT-ASHTAKA CHURNA AS A VIRECHAKA YOGA IN THE MANAGEMENT OF TAMAKA SHWASA (BRONCHIAL ASTHMA) - Parappagoudra, *Mahesh M; Imlikumba, Dr; Lohith, B.A.; Ashvinikumar, M.; Lalravi, S (International Journal of Ayurveda and Pharma Research, 2016)
Virechana Karma is one of the prime modality of the treatment in Panchakarma. Different types and forms of Virechana Yogas are mentioned with specific indications in classics. The trail drug Trivrt Ashtaka Churna is one of the such Virechana Yoga told in our classic. Clinical validation of this drug is further requires, scientific explanation and justification for its global acceptance as a Virechaka Yoga. Tamaka Shwasa occurs mainly due to vitiation Kapha Vata Doshas in Pitta Sthana. It shows close resemblance with Bronchial Asthma on the basis of clinical manifestations. Managing Bronchial asthma on Ayurvedic line of treatment is totally different from that of conventional management. Virechana Karma is the best modality in management of Tamaka Shwasa. Hence the present study has been taken up to see the efficacy of trail drug Trivrt Ashtaka Churna on 30 cases of Tamaka Shwasa (Bronchial Asthma). Results: The study observations showed that the100% good palatability for Virechana Yoga, 64.3% patients got their first Vega on an average time 30 minutes, in 57.1% patients 16 - 18 Vegas were noted, Samyak Shuddi Lakshana with Pittanta was observed in 57.1% of patients.There was a highly significant improvement in symptoms like Swasa krichrata, Kasa, Ghurghuraka, Kaphanishtivana and in signs like Ronchi, Wheeze and Respiration rate got highly significant results (at p<0.001). Conclusion: After going through the clinical changes observed during and after the treatment, it may be opined that, Trivrt Ashtaka Churna acts as a Virechaka Yoga significantly in the management of signs and symptoms of Tamaka Shwasa.